ANALISIS HALAL MEDIA TERHADAP PERUSAHAAN SIARAN MQFM - Reni Rahmawati; Siti Julaicha; Siti Komala N; Sopi Sopiah (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam UIN Sunan Gunung Djati Bandung, 2021)
This paper aims to explain more about the results of direct interviews with MQFM as a media that is considered as a halal industry in the halal field of media. Halal industry is an activity of processing or processing products by using facilities and equipment that are permitted by Islamic sharia, in which there are many derivatives. One of them is halal media. In the era of globalization which is marked by the rapid development of the technology world, many new media developments have emerged or also existing media in advance but continue to upgrade themselves. Indonesia is a Muslim majority country, halal is an indicator of consideration in consuming or making a sound. Here halal has a broad meaning, not just food, but all aspects must have halal elements. In halal media itself there are several indicators of a media that can be said halal.Keywords: Halal media, Halal industry, MQFM